Investigation of Physical and Mechanical Properties and Their Relationship in Senegalia caffra Wood Grown in Northern Ethiopia - Waktole, Samson; Mussa, Mahadi; Abara, Lamesa; Wale, Misganaw; Mogninet, Kassahun (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2025)
This research focused on determining the physical and mechanical properties of Senegalia caffra collected from a Gilgile Beles site in Ethiopia and analyzing how these properties relate to the wood's performance. Fifteen (15) sample trees were selected and felled for the study. Sampling, specimen preparation, and conducting the different tests were achieved following ISO and British standards. In this study, the mean basic density of 594.40 Kg/m3, modulus of elasticity (MoE) of 9,556.79 N/mm2, modulus of rupture (MoR) of 105.69 N/mm2, compression strength parallel to the grain of 53.15 N/mm, impact bending strength of 14,825.00 Nm/m2, radial and tangential hardnesses of 4,958.67 N and 5,324.78 N, respectively, were obtained for the species. Senegalia caffra was superior to the high timber-value tree species of Ethiopia in most of the studied features. The bottom of the tree was highest in density, MoE, MoR, radial, and tangential hardnesses; whereas, the middle height was higher in compression and impact bending strengths. Heartwood was higher in density, MoE, compression strength, and radial and tangential hardnesses than sapwood. Density was moderately correlated with radial hardness (with an R of 0.605 and sig. of 0.000). Generally, higher properties were recorded at the bottom of the tree as well as in the heartwood.